Caring for justice in a neoliberal university - Hölscher, D. (South African Journal of Higher Education, 2018)
This article is based on a study on participatory parity in higher education in South Africa. Its purpose is to explore the nature of the relationship between care and social justice under conditions of neoliberalism. Using the lenses of Joan Tronto’s democratic ethics of care and Nancy Fraser’s work on social justice, I also reflect on my own practices as a social work lecturer in a university that has a high percentage of students who, by their own accounts, are poor. Based on the study’s findings and my reflections thereupon, I argue that the context of higher education in South Africa renders relationships between students and lecturers vulnerable to replicating and reinforcing prevailing injustices in the sector. However, in the face of such entanglement, to care emerges as subversive practice, apt to substitute some of the key conditions and processes at the root of the injustices afflicting the field. I conclude that a democratic ethics of care can be employed to further the ends of social justice against the odds of a neoliberal learning context. This will also contribute to enhancing the well-being and academic development of both students and staff.